A Case of Delayed Diagnosis of Bilateral Ureteral and Bladder Injury after Laparoscopic Hysterectomy: An Unusual Complication. (6th November 2012) - Goris-Gbenou, Maximilien C.; Arfi, Nicolas; Mitach, Abdel; Rashed, Sheer; Lopez, Jean-Gabriel
Abstract : The incidence of ureteral and bladder lesions after laparoscopic hysterectomy is the most encountered urinary complication in gynaecological surgery. We report the unusual case of 42-year-old woman who had a delayed diagnosis of bilateral ureteral injury associated with bladder lesion and loose of vaginal suture after undergoing laparoscopic hysterectomy for uterine adenomyosis.